DIPONEGORO AND THE ULAMA NUSANTARA NETWORK - Zainul Milal Bizawie (The International Journal of Pegon : Islam Nusantara civilization, 2020)
The Javanese War was the event of the greatest resistance of the Javanese against the colonial authorities. As the last form of 'old order' resistance, the Java War witnessed the disarmament of the southern central Java palaces when their territories in eastern countries were finally annexed (1830-1831) (Houben 1994: 17-72). At the end of the war, Dutch control of Java was still unchallenged. Their role only ended 112 years later (1830-1942). That, too, was in the hands of the Japan (March 9, 1942), disputing only one day with the day when Diponegoro entered the city of Magelang to conduct a "peace negotiation" (March 8-28, 1830) with De Kock (Carey 2014: 338). In the Java war, Javanese identity became a key factor in the enthusiasm of Diponegoro's supporters like Meiji Restoration in Japan. Besides upholding the dignity of the Islamic religion, restoration of Javanese values in particular was a key priority, which also encouraged enmity towards non-Javanese during the war, especially to the Netherlands. The alliance of knights (ksatria) and muslim students (santri) built by Diponegoro has inspired a five-year war that seeks social support that is very broad and unique with religious fervor. Even after the Java War, the Dutch regarded the holy war clothing as a symbol of subversion crime for Javanese aristocrats (Carey, 2017: 166). The last remnants of the Diponegaran family were removed from the palace. This means, the Dutch Colonial continued to try to separate the Diponegaran breed from the religious scholars (Ulama), keeping the remaining Diponegoro knights from the santri network scattered in various parts of Java. This paper will explore the network of Diponegoro ulama-santri (scholars-students), although many of the characters have already been mentioned. Also provides another perspective in reading differences of opinion and strategy from Diponegoro and Kyai Mojo along with a network of ulama-santri in building an Islamic Balad (region/city/land), which in essence has the same goal, namely to synergize Islam and the order of society, to construct an Islamic Nationality which was later in the hands of Hadratus Syekh Hasyim Asy'ari and other scholars succeeded in being built to uphold the Republic of Indonesia. Then, who continues the restoration of the glory of Islam in Java and connects with it outside Java? Of course it cannot be explained by exposing its descendants who for nearly a century were chased and lived in coincidence because they were hunted down by the Dutch Colonial. One thing that was instilled by Diponegoro was that he did not see any inherent conflict between the Javanese spiritual realm and its position as part of the world's Muslims, whose centers were in Hijaz (Saudi Arabia) and Ottoman Turkey. Therefore, it is not a coincidence that the ulama or the santri community then built a network in Haramain throughout the Ottoman Mufti in the Hijaz, which would later be known by the Javanese community (jama'ah al Jawiyyin) which led to the emergence of figures such as Hadratus Syekh Hasyim Asy’ari. The existence of Hasyim Asy'ari opened the veil of how his scientific network was connected with his struggle network to the paramilitary forces of the Diponegoro ulama-santri and knights also connected with other archipelago (nusantara) scholars, even worldwide, as well as connecting to sanad (scientific continuity) to previous scholars. Therefore, going through the network and sanad is very important to fade the awesome power of the spirit of Islam in building national values in Indonesia, which is different from the building of nationalism in Western countries. The spirit of Islam is inherited and maintained in the network and sanad of the scholars who succeeded in forming a unique Islamic character in Indonesia. The Diponegoro ulama network has become a crucial point in the progress of Nusantara's ulama-santri in caring for Islamic traditions in the nusantara and widespread throughout the Nusantara in mecca. Their works have become the main reference for learning systems in surau, pesantren and madrasa to date. The works are a historical legacy which is the mouth of cosmology of thought, the dynamics of knowledge and the accumulation of the culture of Jawi scholars and pesantren in this country. Tulisan ini akan mengeksplorasi jaringan ulama santri Diponegoro, meskipun dalam tokoh-tokohnya telah banyak disinggung. Juga memberikan perspektif lain dalam membaca perbedaan pendapat dan strategi dari Diponegoro dan Kyai Mojo berikut jejaring ulama santrinya dalam membangun Balad Islam, yang pada intinya memiliki tujuan sama, yaitu mensinergikan Islam dan tatanan masyarakat, mengkonstruk sebuah Islam Kebangsaan yang di kemudian hari di tangan Hadratus Syekh Hasyim Asy’ari dan para ulama lainya berhasil dibangun untuk menegakkan NKRI. Lantas, siapakah yang melanjutkan restorasi kejayaan Islam di Jawa dan mengkoneksikannya dengan luar Jawa? Tentu saja tidak dapat dijelaskan dengan mengungkap para keturunannya yang selama hampir seabad dikejar-kejar dan hidup dalam keterhimpitan karena diburu Kolonial Belanda. Satu hal yang ditanamkan Diponegoro adalah ia tidak melihat ada konflik yang melekat antara alam spiritual Jawa dan kedudukannya sebagai bagian dari umat Islam di dunia, yang pusat-pusatnyya berada di Hijaz (Arab Saudi) dan Turki Usmani. Oleh karena itu, bukan suatu kebetulan para ulama atau kalangan santri kemudian membangun jaringan di Haramain dalam penjuru para mufti Turki Usmani di Hijaz, yang nantinya dikenal komunitas Jawa (jama’ah al Jawiyyin) yang berujung munculnya tokoh seperti Hadratus Syekh Hasyim Asy’ari. Keberadaan Hasyim Asy’ari membuka tabir betapa jejaring keilmuannya bersambung dengan jejaring perjuangannya ke laskar para santri dan ksatria Diponegoro juga terhubung dengan ulama nusantara lainnya, bahkan telah mendunia, sekaligus menghubungkan pada sanad kepada ulama-ulama sebelumnya. Karena itu, menyusuri jejaring dan sanad tersebut sangat penting untuk mengudar kekuatan dahsyat dari spirit Islam dalam membangun nilai-nilai kebangsaan di Indonesia, yang berbeda dengan bangunan nasionalisme di negara-negara Barat. Spirit Islam itu terwariskan dan terjaga dalam jejaring dan sanad para ulama yang berhasil membentuk karakter keislaman yang khas di Nusantara. Jejaring ulama Diponegoro menjadi titik krusial kiprah ulama-santri Nusantara dalam merawat tradisi Islam di Nusantara dan menusantara di haramain. Karya-karya mereka menjadi referensi utama sistem pembelajaran di surau, pesantren dan madrasah hingga saat ini. Ulama Jawi menulis teks dengan menggunakan aksara Pegon, yakni beraksara Arab namun dengan bahasa Jawa. Kitab-kitab Pegon inilah yang menjadi tradisi pengetahuan dan formasi teks yang kokoh sebagai sistem komunikasi ulama untuk melawan kolonialisme. Kitab-kitab Pegon menjadi warisan sejarah yang menjadi muara kosmologi pemikiran, dinamika pengetahuan dan akumulasi kebudayaan ulama Jawi dan pesantren di negeri ini.